ʽIsolated Mass Hermitsʼ: Individualization and Communication in the Risk Society - Lombardinilo, Andrea (Italian Sociological Review, 2022)
This essay gives an insight into the effects of cosmopolitan individualization that Ulrich Beck investigates in chapter 5 of Risk Society, thus anticipating some of the sociological findings in some of his last books, e.g. A God of One’s Own and The Metamorphosis of the World. To the fore is the relationship between the new ʽcommunication landscapesʼ and the process of fragmentation of daily life fuelled by hyperconnectivity and mainstream narration. Accordingly, technological acceleration led to the construction of biographical paths inspired by a new relational solipsism, so common in the era of globalized risks and cultural obsolescence. The metaphor of ʽisolated mass hermitsʼ gives a better understanding of the tendency to personalize faith and spiritual practices, in line with some unexpected interactional techniques. According to Beck, scholars have the duty to analyse ʽthe subjectivization and individualization of risks and contradictions produced by institutions and societyʼ. In this perspective, communicative risks interlace with value and cultural shortcomings, even though secularization and laicization find their foundation in the historical background of Western societies. This is why Beck’s ʽisolated mass hermitsʼ are the prelude to the diffusion of an “isolated mass audience”, whose social impact can be surveyed through the analysis of institutionalized biographical narrations.